A new species of Aspidoras Ihering (Siluriformes: Callichthyidae: Corydoradinae) from the Rio Xingu Basin, Pará, Brazil - Leão, Manuela D. V.; Britto, Marcelo R.; Wosiacki, Wolmar B. (Zootaxa, 2015)
A new species of Aspidoras is described from an unnamed stream in the Rio Xingu Basin, Castelo de Sonhos municipality, Pará State, representing the northernmost record of the genus along the edge of the Brazilian Shield in the Amazon Basin. Aspidoras marianae is easily distinguished from all congeners in having minute odontode-bearing platelets scattered over the surface of the snout region, minute platelets between the parieto-supraoccipital process and the nuchal plate, and other shared features related to color pattern, morphometrics, meristics and morphological data. Comments about exclusive and shared features are presented.